New records of bee genera (hymenoptera: apoidea) from colombia (2006)
The solitary bee genera Lophothygater Moure y Michener (Apidae, Eucerini) and Tapinotaspoides Moure (Apidae, Tapinotaspidini) are reported from northern Colombia for the first time. These genera were previously known from the central Brazilian Amazonian and Argentina and Paraguay, respectively.